Why governments intervene: Exploring mixed motives for public policies on corporate social responsibility. (January 2015) - Knudsen, Jette S; Brown, Dana
Why are national governments increasingly adopting policies on corporate social responsibility (CSR)? Government CSR policies have been explained either as a means of substituting or supporting (mirroring) domestic political-economic institutions and policies, or as a means for government to promote international competitiveness of domestic businesses. Both sets of explanations see governments as driving CSR policies to meet particular national government goals. Support is found for the thesis that CSR policies are often related to international competitiveness, yet our findings suggest that government goals in this regard are not necessarily pre-defined.